Kinetics and product identification of water-dissolved nitroguaiacol photolysis under artificial sunlight - Delić, Ajda; Skube, Urša; Šala, Martin; Kroflič, Ana (Frontiers in Chemistry, 2023)
Nitroguaiacols are typical constituents of biomass-burning emissions, including absorbing aerosols which contribute to climate change. Although they are also harmful to humans and plants, their atmospheric fate and lifetimes are still very speculative. Therefore, in this work, the photolysis kinetics of aqueous-phase 4-nitroguaiacol (4NG) and 5-nitroguaiacol (5NG), and the resulting photo-formed products were investigated under artificial sunlight, observing also the effect of sunlight on the absorption properties of the solutions. We found the photolysis of 5NG slower than that of 4NG, whereas the absorbance in the visible range prevailed in the 5NG solutions at the end of experiments. Although we identified dinitroguaiacol as one of the 4NG photolysis products, which increased light absorption of 4NG-containing solutions, considerably more chromophores formed in the 5NG photolyzed solutions, implying its stronger potential for secondary BrC formation in the atmosphere. In general, denitration, carbon loss, hydroxylation, nitration, and carbon gain were characteristic of 4NG phototransformation, while carbon loss, hydroxylation, and carbon gain were observed in the case of 5NG. The photolysis kinetics was found of the first order at low precursor concentrations (<0.45 mM), resulting in their lifetimes in the order of days (125 and 167 h illumination for 4NG and 5NG, respectively), which suggests long-range transport of the investigated compounds in the atmosphere and proposes their use as biomass-burning aerosol tracer compounds.